STUD I KA SUS MIGRASI DI PAPUA PERKEMBANGAN KOTA HOLLANDIA 1944 - 1962 - Hari Suroto (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
Holandia was once a village that when the Pacific war happened, it changed rapidly into a modern city. Hollandia was made as headquarters for the allied armed forces. Then it developed and the population increased rapidly because of urbanization that made many social problems appeared. The rapid changes in culture and custom in Hollandia were generally objected by the natives. They showed their disappointment to the Dutch and its Allies whom they thought as the causes of the fast and confusing changes.